A Case Study On Corporate Restructuring In Malaysia - Lion Group - Min, Chew Lee (2005)
This study analyzes the result of Lion Group's corporate restructuring since 1996 till 2003. The research finds that restructuring is a lenghty process, with the restructuring period occurring prior to the definitive proposals for corporate change. In the case of Lion group, the restructuring work has started since 1998 and lasted more than 5 years before the proposal of corporate and debt restructuring exercises was finalized and announced in January 2003.